Change of “Left atrium ejection force” after transcatheter “Atrial septal defect” closure using “AMPLATZER,” in pediatric patients - Hassan Esmaeili; Kourosh Vahidshahi; Maryam Moradian; Hojjat Mortezaeian (Research in Cardiovascular Medicine, 2018)
Background and Purpose: There has not been any study regarding atrial systolic function in transcatheter atrial septal defect (ASD) closure. The aim of this study was to survey left atrium ejection force in this procedure in the pediatric age group. Subjects and Methods: This was an observational (before and after) study. Pediatric patients who underwent transcatheter ASD closure using “AMPLATZER” at “Rajaei Cardiovascular Medical and Research Center,” from March to December 2013, were enrolled consecutively. Physical examination and transthoracic echocardiography were performed for the patients before and 12–24 h after the procedure, and left atrium ejection force was calculated. Results: Totally, 63 patients (age: 6.11 ± 3.43 [1–14] years and weight: 21.53 ± 10.79 [9.7–48] kg) were studied. ASD size was 11.43 ± 3.30 (5–22) mm. Left atrium ejection force, before and after the procedure, was 7.19 ± 6.06 (0.33–32.54) kilodyne and 6.30 ± 4.03 (0.5–18.16) kilodyne, respectively (P = 0.28). There was no significant difference between pre- and postprocedure left atrium ejection force in different age group, both genders, types of the device, and ASD size. Postprocedure left atrium ejection force was significantly lower in the patients with large devices (diameter of left atrial disk to body surface area ratio index >40 mm/m2) than smaller device. Conclusion: This study showed that left atrium ejection force after transcatheter ASD closure does not change significantly at early stage, so atrial systolic function is maintained in the presence of the device. In the patients with large device, left atrium ejection force may decrease.